Features of binding sites of miR-574-5p and miR-574-3p with target genes mRNAs (Experimental biology, 2016)
The binding of miR-574-5p and miR-574-3p with their target genes mRNAs was studied. miR-574-5p binding sites are located in the 3'UTR of 244 genes, in the 5'UTR of 20 genes and in the CDS of two genes. miR-574-5p binding sites in the CDS of REM2 and FGFRL1 genes with the high ΔG/ΔGm value encode oligopeptides HTHTHTHS and DTDMDTDT in the corresponding proteins. miR-574-3p bindingsites are located in the 3'UTR of genes GRK6, NACC2, SEC14L1 and in the 5'UTR of the gene ZNF470. In the majority of miR-574-5p target genes mRNAs there are multiple binding sites with the ΔG/ΔGm valuegreater than 90%, which arranged located through two nucleotides. Changes in the miR-574-5p and miR-574-3p expression at many pathologies, including cancer, correlated with changes in the expression of their target genes.
Keywords: miRNA; mRNA; miR-574-5p; miR-574-3p; binding sites; target genes.